2000
DOI: 10.1038/sj.bjp.0703568
|View full text |Cite
|
Sign up to set email alerts
|

Vascular bed heterogeneity in age‐related endothelial dysfunction with respect to NO and eicosanoids

Abstract: 1 Endothelial dysfunction has been described with ageing but the mechanisms responsible have not been clearly elucidated and might be di erent from one vessel to the other. This study assesses the relative contribution of endothelial nitric oxide (NO) and cyclo-oxygenase (COX) metabolites in relaxation to acetylcholine with ageing in the aorta and the small mesenteric artery of the rat. 2 In the aorta and branch II or III of superior mesenteric artery (SMA), endothelium-dependent relaxation to acetylcholine wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
110
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(123 citation statements)
references
References 28 publications
11
110
0
2
Order By: Relevance
“…Thus, in normotensive individuals, an earlier primary dysfunction of the NO pathway and a later production of oxidative stress cause age-related reduction in endothelium-dependent vasodilation; these alterations are similar but earlier in hypertensive patients compared with normotensive subjects (53). Furthermore, enhanced oxidative stress plays a critical role in the deleterious effect of aging on the endothelium through acceleration of NO breakdown by reactive oxygen species (8)(9)(10)(11)(12)(13)(14). Increased oxidative stress also occurs during vascular response to PTCA (54,55).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, in normotensive individuals, an earlier primary dysfunction of the NO pathway and a later production of oxidative stress cause age-related reduction in endothelium-dependent vasodilation; these alterations are similar but earlier in hypertensive patients compared with normotensive subjects (53). Furthermore, enhanced oxidative stress plays a critical role in the deleterious effect of aging on the endothelium through acceleration of NO breakdown by reactive oxygen species (8)(9)(10)(11)(12)(13)(14). Increased oxidative stress also occurs during vascular response to PTCA (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…However, routine clinical management using pure NO donors could be difficult because of systemic effects on blood pressure. The mechanisms underlying restenosis are further complicated by vascular aging (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Decreased vasorelaxation caused by a decline in NO and endothelium-derived hyperpolarizing factor, as well as increased vasoconstriction mediated by cyclooxygenase products such as thromboxane A2, and concomitantly increased sensitivity of apoptosis, are likely to occur in aging (5-14, 52).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that through the activation of TP receptors, vasoconstrictor prostanoids such as TXA 2 can participate in the endothelial dysfunction associated with different cardiovascular risk factors. 30,32,34 Incubation with SQ 29 548, a TP receptor antagonist, increased ACh relaxations in both strains of rats treated with aldosterone in a comparable manner, suggesting the participation of vasoconstrictor prostanoids through TP receptors. However, the present results showed that in aorta from WKY and SHR treated with aldosterone, TXA 2 is not an important candidate responsible for the reduction of endothelium-dependent relaxations.…”
mentioning
confidence: 99%